2019
DOI: 10.21276/ijcmsr.2019.4.2.27
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sinonasal Anatomical Variants using 128-Slice MDCT in Patients with Chronic Rhinosinusitis

Abstract: To investigate the prevalence of anatomic variants of the sinonasal cavities using 128-slice-Multidetector CT and to determine their relation to sinonasal mucosal disease. Material and methods: A total of 200 patients were included. The inclusion criteria were patients with clinical symptoms of chronic rhinosinusitis and e exclusion criteria were patients with history of trauma, sinus surgery and sinonasal tumours and patients with contraindications for CT like pregnancy. All the patients with symptoms of chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This was similar to Wani et al's study, which found concha bullosa in 30% of patients [19]. However, Gouripur et al [20] found concha bullosa in 12% of cases while Mathuram et al [21] found it in 43.5% of cases.…”
Section: Discussionsupporting
confidence: 86%
“…This was similar to Wani et al's study, which found concha bullosa in 30% of patients [19]. However, Gouripur et al [20] found concha bullosa in 12% of cases while Mathuram et al [21] found it in 43.5% of cases.…”
Section: Discussionsupporting
confidence: 86%
“…The frontal sinuses are located in the posterior most part of supercilliary arches, between the external and internal tables of frontal bone. Presence of bilateral frontal sinus was reported in (78.6%) subjects and presence of unilateral frontal sinus was found to be present in (17.9%) subjects 23 .…”
Section: Literature Reviewmentioning
confidence: 93%
“…The development of PNS starts from furrows and ridges in the lateral wall of nasal cavity during 8 th week of development, and sinuses continue their formation as air cells within the cavities until early adulthood from the age of 20 to 25 years. Each sinus is named according to the skull bone in which they are located 1,23 .…”
Section: Literature Reviewmentioning
confidence: 99%